Depression: A Gut "Microbiome" Feeling!. Issue 9 (September 2021) - Naguy, Ahmed; Pridmore, Saxby; Abuzeid, Mohamed Y.; Thiguti, Sri Haricharan; Alamiri, Bibi
Abstract: Burgeoning body of evidence from neuroscience is pouring in highlighting a potential association between gut microbiota with the pathophysiology of depression and anxiety. Manipulation of gut microbiota may be then useful to decode this role and to provide novel therapeutics for major depressive disorder (MDD), developing microbiota-related biomarkers to stratify patients at risk and to delineate more homogeneous biotypes of MDD.